Synthesis and Study the Impact of Annealing Temperature on Structural, Electrical and Gas Sensing Properties of LaCrO3 Thick Films - Handge, S. B.; Shinde, U. P.; Halwar, D. K. (Journal of Scientific Research, 2025)
In this work, LaCrO3 nanostructure were modified with annealing temperature. The present work deals with the study of the impact of annealing temperature on the structural, electrical and gas sensing properties of LaCrO3 thick films. The thick films of LaCrO3 were developed on glass substrate by screen printing technique. The LaCrO3 nanostructure was synthesized by sol–gel method. The characterizations were carried out by using standard tools like X-ray diffraction (XRD), energy-dispersive X-ray (EDX) and scanning electron microscopy (SEM) revealed the confirmation of a crystal structure, elemental analysis and the morphology of synthesized LaCrO3 respectively. The impact of annealing temperature on selected properties of LaCrO3 thick films were successfully studied. The investigation suggested that, the annealed thick films possess better results than unannealed films. The developed LaCrO3 thick films were used to detect various hazardous air pollutants such as NO2, CH4, LPG, ethanol, NH3 and petrol vapor. LaCrO3 thick films shows maximum sensitivity to nitrous oxide gas at operating temperature 160 °C. The films also demonstrated quick response and recovery time.